FSMP-17. GLOBAL METABOLOMIC PROFILING OF GLIOBLASTOMA MULTIFORME REVEALS METABOLIC VULNERABILITIES IN RESPONSE TO RADIATION THERAPY. (25th March 2021) - Durairaj, Aarooran; McReynolds, Melanie; Wang, Congcong; He, Joy; Rabinowitz, Joshua; Andreasson, Katrin; Minhas, Paras
Abstract: Glioblastoma multiforme (GBM), the most aggressive primary brain tumor, originates in astrocytes and oligodendrocytes and yields a median survival time of less than 2 years and a 5-year survival of 2.5%. There has been little in the way of treatments and novel approaches are needed to combat the poor prognosis of GBM. Recent studies have established that GBM cells exhibit metabolic reprogramming to adapt to diverse metabolic gradients within heterogenous tumor microenvironments. Using an unbiased metabolomics approach, we investigated metabolic changes both pre- and post-ionizing radiation across several patient-derived GBM cell lines. Surprisingly, acute high dosage of ionizing radiation resulted in significant changes in the synthesis of aminolevulinic acid (ALA), a non-proteinogenic amino acid. Fractionation of radiation therapy resulted in dose-dependent changes in the heme synthesis pathway within these cells. Using an orthotopic xenograft mouse model of GBM, we identify several enzymatic vulnerabilities in vivo and discuss a novel combinatorial therapeutic approach of radiation and targeted pharmacological intervention. Our findings reveal the fundamental biosynthetic changes that GBMs adopt when exposed to ionizing irradiation as well as the benefits of a combinatorial approach.